(untitled) (Journal of Information Technologies in Education (ITE), 2013)
The problems and perspectives of the cloud computing usage in education are investigated in the paper. The examples of the most popular cloud platforms such as Google Apps Education Edition and Microsoft Live@edu used in education are considered. The schema of an interaction between teachers and students in cloud is proposed. The abilities of the cloud storage such as Microsoft SkyDrive and Apple iCloud are considered.